Assessment of Xpert Bladder Cancer Monitor test performance for the detection of recurrence during non-muscle invasive bladder cancer follow-up - Cancel-Tassin, G.; Roupret, M.; Pinar, U.; Gaffory, C.; Vanie, F.; Ondet, V.; Compérat, E.; Cussenot, Olivier (World journal of urology, 2021)
Purpose To assess the performance of the Xpert Bladder Cancer (BC) Monitor during the follow-up of patients with non-muscle invasive bladder cancer (NMIBC). Methods Patients with previously diagnosed NMIBC and followed up in clinical practice settings in two French urology departments between September 2017 and July 2019 were consecutively enrolled in this prospective observational study. Patients with a positive cystoscopy or computed tomography urogram underwent subsequent transurethral resection of the bladder, and/or biopsy, and the specimens were pathologically assessed. Cytology and Xpert BC Monitor tests were performed on urine samples. Xpert BC Monitor performance was assessed versus cystoscopy for disease-negative patients or versus histology for disease-positive patients, and was compared to that of cytology. Results Overall, 500 patients with a median age of 70.0 years were included. NMIBC recurrence was diagnosed in 44 cases (8.8%). Overall sensitivity, specificity, and negative predictive values (NPVs) were 72.7% (32/44), 73.7% (330/448) and 96.5% (330/342) for the Xpert BC Monitor, and 7.7% (2/26), 97.8% (310/317) and 92.8% (310/334) for cytology, respectively. The Xpert BC Monitor detected 92.3% (12/13) of the high-grade tumours and ruled out their presence in 99.7% (330/331) of cases. Analysis of the areas under the receiver operating characteristic curves demonstrated the superior performance of the Xpert BC Monitor over that of cytology. Conclusion Xpert BC Monitor performance was superior to that of cytology in the follow-up of NMIBC. The exclusion of aggressive tumours with a very high NPV (99.7%) supports the use of this urinary test in daily practice.